2017
DOI: 10.2147/dddt.s133759
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of stroke patients receiving different doses of recombinant tissue plasminogen activator

Abstract: Background and purpose Intravenous recombinant tissue plasminogen activator (tPA) at a dose of 0.9 mg/kg body weight is associated with a high hemorrhagic transformation (HT) rate. Low-dose tPA (0.6 mg/kg) may have a lower hemorrhage rate but the mortality and disability rates at 90 days cannot be confirmed as non-inferior to standard-dose tPA. Whether the doses 0.7 and 0.8 mg/kg have better efficacy and safety needs further investigation. Therefore, this study is to compare the efficacy and safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Eleven studies with a total of 3,539 subjects, including 373 patients with END and 3,166 patients without END, met the inclusion and exclusion criteria. Of these studies, there were 4 studies from Asia (Chi & Chan, 2017;Mori et al, 2012;Ong et al, 2017;Yang et al, 2016), 6 studies from Europe (Fiorelli et al, 1999;Hansen, Christensen, Havsteen, Ovesen, & Christensen, 2018;Seners et al, 2014Seners et al, , 2017Simonsen et al, 2016;Zinkstok et al, 2014), and 1 study from North America (Saqqur et al, 2007). The baseline characteristics of all the included studies were shown in Table 1.…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies with a total of 3,539 subjects, including 373 patients with END and 3,166 patients without END, met the inclusion and exclusion criteria. Of these studies, there were 4 studies from Asia (Chi & Chan, 2017;Mori et al, 2012;Ong et al, 2017;Yang et al, 2016), 6 studies from Europe (Fiorelli et al, 1999;Hansen, Christensen, Havsteen, Ovesen, & Christensen, 2018;Seners et al, 2014Seners et al, , 2017Simonsen et al, 2016;Zinkstok et al, 2014), and 1 study from North America (Saqqur et al, 2007). The baseline characteristics of all the included studies were shown in Table 1.…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…The baseline characteristics of all the included studies were shown in Table 1. Four studies provided the type and dose of the thrombolytic drug (Fiorelli et al, 1999;Mori et al, 2012;Ong et al, 2017;Yang et al, 2016), and the remaining studies provided insufficient information of the thrombolytic drug (Chi & Chan, 2017;Hansen et al, 2018;Saqqur et al, 2007;Seners et al, 2014Seners et al, , 2017Simonsen et al, 2016;Zinkstok et al, 2014) (Table 2).…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…IVT has been reported to increase the incidence of HT markedly [7]. Atrial fibrillation (AF) [8,9], National Institutes of Health Stroke Scale (NIHSS) score [10], blood glucose level [11], leukoaraiosis [12], dual antiplatelet agent treatment before IVT [13], and systolic blood pressure variability [14] are the predictors of HT after IVT.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Studies reported that the efficacy and safety of low-dose tPA were comparable with that of standard-dose tPA. [11][12][13][14][15] However, some studies reported that stroke patients receiving standard dose tPA had higher rates of favorable outcome and without significantly increased risk of symptomatic hemorrhage and mortality when compared with those of patients receiving low-dose tPA. [16][17][18] In the Enhanced Control of Hypertension and Thrombolysis Stroke Study (ENCHANTED) study, the investigators compared the effect of low-dose (0.6 mg/kg) with standard-dose IV tPA on the outcomes in patients with ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%